Local Optimum Distance Evaluated Simulated Kalman Filter For Combinatorial Optimization Problems - Zulkifli, Md. Yusof; Ismail, Ibrahim; Zuwairie, Ibrahim; Khairul Hamimah, Abas; Nor Azlina, Ab. Aziz; Nor Hidayati, Abd Aziz; Mohd Saberi, Mohamad (Universiti Malaysia Pahang, 2016)
Inspired by the estimation capability of Kalman filter, we have recently introduced a novel estimation-based optimization algorithm called simulated Kalman filter (SKF). Every agent in SKF is regarded as a Kalman filter. Based on the mechanism of Kalman filtering and measurement process, every agent estimates the global minimum/maximum. Measurement, which is required in Kalman filtering, is mathematically modelled and simulated. Agents communicate among them to update and improve the solution during the search process. However, the SKF is only capable to solve continuous numerical optimization problem. In order to solve combinatorial optimization problems, an extended version of SKF algorithm, which is termed as Local Optimum Distance Evaluated Simulated Kalman Filter (LODESKF), is proposed. Similar to existing approach, a mapping function is used to enable the SKF algorithm to operate in binary search space. A set of traveling salesman problems are used to evaluate the performance of the proposed LODESKF against DESKF